2015
DOI: 10.1186/s40659-015-0037-4
|View full text |Cite
|
Sign up to set email alerts
|

Anticancer properties and enhancement of therapeutic potential of cisplatin by leaf extract of Zanthoxylum armatum DC.

Abstract: BackgroundClinical use of chemotherapeutic drug, cisplatin is limited by its toxicity and drug resistance. Therefore, efforts continue for the discovery of novel combination therapies with cisplatin, to increase efficacy and reduce its toxicity. Here, we screened 16 medicinal plant extracts from Northeast part of India and found that leaf extract of Zanthoxylumarmatum DC. (ZALE) induced cytotoxicity as well as an effect on the increasing of the efficiency of chemotherapeutic drugs (cisplatin, mitomycin C and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(22 citation statements)
references
References 21 publications
1
19
0
2
Order By: Relevance
“…Vários estudos etnobotânicos documentaram os diferentes usos etnomedicinais dos extratos e infusões obtidos das cascas, sementes e frutos de Z. alatum no tratamento de diferentes tipos de doenças. Na Índia, onde é conhecido por mukthrubi, é utilizado na preparação de medicamentos indígenas contra várias doenças como asma, bronquite, indigestão, veias varicosas, diarreia , reumatismo, dispepsia e cólera (Singh et al 2015, Nooreen et al 2017. No Nepal é usado contra dor de dente, diabetes, problemas estomacais (Balami, 2006), intoxicação alimentar (Malla et al 2014) e tuberculose (Subedi 2017).…”
Section: Zanthoxylum Alatum Hemslunclassified
“…Vários estudos etnobotânicos documentaram os diferentes usos etnomedicinais dos extratos e infusões obtidos das cascas, sementes e frutos de Z. alatum no tratamento de diferentes tipos de doenças. Na Índia, onde é conhecido por mukthrubi, é utilizado na preparação de medicamentos indígenas contra várias doenças como asma, bronquite, indigestão, veias varicosas, diarreia , reumatismo, dispepsia e cólera (Singh et al 2015, Nooreen et al 2017. No Nepal é usado contra dor de dente, diabetes, problemas estomacais (Balami, 2006), intoxicação alimentar (Malla et al 2014) e tuberculose (Subedi 2017).…”
Section: Zanthoxylum Alatum Hemslunclassified
“…Z. armatum dried An Overview of Genus Zanthoxylum with Special Reference to Its Herbal Significance… DOI: http://dx.doi.org /10.5772/intechopen.92459 root ethyl acetate extract (EAE) (a good antioxidant) and its two components flavonoids, apigenin and kaempferol-7-O-glucoside, also possess an anticancerous trait against A-549, MIA-PaCa, MCF-7, and CACO 2 cancer colon cell lines [40]. In an extensive study, the ME of leaf of Z. armatum induced apoptosis in cervical cancer cell lines (HeLA) at IC 50 (60 μg/mL) through Caspase 3-independent and extracellular signal-regulated kinases (ERK)-dependent mitogenactivated protein kinases (MAPK) apoptosis pathways [41]. Karmakar et al [42] demonstrated that at an IC 50 value of 102.30 μg/mL, the ME of the leaves of Z. armatum exhibited toxicity against Ehrlich Ascites cancer cells.…”
Section: Zanthoxylum As Herbal Medicine In Modern Pharmacology 41 Anmentioning
confidence: 99%
“…Zanthoxyllum armatum leaf extract have the potential effect on increasing the efficiency of chemotherapeutic drugs like camptothecin, mitomycin C and cisplatin. 34 In this study, HeLa cells with 80µg/ml was treated with ZALE for almost 48 hours. It shows morphological changes and cytotoxicity in dose dependent manner.…”
Section: Cytotoxicitymentioning
confidence: 99%